A comprehensive review on NUI, multi-sensory interfaces and UX design for applications and devices for visually impaired users - Arora, Lauryn; Choudhary, Akansh; Bhatt, Margi; Kaliappan, Jayakumar; Srinivasan, Kathiravan (Frontiers in Public Health, 2024)
In today’s world, there has been a significant increase in the use of devices, gadgets, and mobile applications in our daily activities. Although this has had a significant impact on the lives of the general public, people who are Partially Visually Impaired SPVI, which includes a much broader range of vision loss that includes mild to severe impairments, and Completely Visually Impaired (CVI), who have no light perception, still face significant obstacles when trying to access and use these technologies. This review article aims to provide an overview of the NUI, Multi-sensory Interfaces and UX Design (NMUD) of apps and devices specifically tailored CVI and PVI individuals. The article begins by emphasizing the importance of accessible technology for the visually impaired and the need for a human-centered design approach. It presents a taxonomy of essential design components that were considered during the development of applications and gadgets for individuals with visual impairments. Furthermore, the article sheds light on the existing challenges that need to be addressed to improve the design of apps and devices for CVI and PVI individuals. These challenges include usability, affordability, and accessibility issues. Some common problems include battery life, lack of user control, system latency, and limited functionality. Lastly, the article discusses future research directions for the design of accessible apps and devices for visually impaired individuals. It emphasizes the need for more user-centered design approaches, adherence to guidelines such as the Web Content Accessibility Guidelines, the application of e-accessibility principles, the development of more accessible and affordable technologies, and the integration of these technologies into the wider assistive technology ecosystem.